Identification of cyber threats in IoV communication: a systematic literature review - Ullah, Naeem; Ahmad, Iftikhar; Almazroi, Abdulaleem Ali; Rahman, Mujeeb Ur (Springer, 2025)
Internet of Vehicles (IoV) plays an essential role in the intelligent transportation system that contributes to traffic congestion reduction, road safety, pollution reduction, and efficient travel. However, the growing reliance on communication technologies subjects IoV to a wide range of cyber threats, such as privacy violations, message malware, spoofing, and denial-of-service attacks. The paper involves a Systematic Literature Review (SLR) to determine and evaluate cyber threats in the IoV communication. After a systematic search and quality evaluation, 83 primary research studies were examined, and as a result, eight key categories of threats were identified. According to the findings, denial-of-service and distributed denial-of-service (DDoS) attacks, spoofing and impersonation, and falsified information attacks are the most reported risks. These insights represent a broad view of the existing vulnerabilities in the communication of the Internet of Vehicles and countermeasures are required to address the identified cyber-threats. The findings of this review would inform other researchers, policy makers, and industry practitioners to establish effective countermeasures to enhance IoV security before its wide-scale implementation.
Keywords: 3509 Transportation, Logistics and Supply Chains; 46 Information and Computing Sciences; 35 Commerce, Management, Tourism and Services; 4604 Cybersecurity and Privacy; Cyber threats; Internet of Vehicles; Vehicular communication; Security; Intelligent Transportation Systems